The benefits of dual-consultant operating in complex breast reconstruction: A retrospective cohort comparison study. Issue 9 (September 2022) - G Forsyth, M.; Taylor, L; Akhtar, A; Samuels, S; Ibradzic, Z; Oni, G; McCulley, S; Rasheed, T; Raurell, A; Tamimy, M
Summary: Background: Dual-consultant operating (DCO) has been introduced in a multitude of surgical specialities. This retrospective cohort comparison study seeks to delineate any benefits DCO may confer on list utilisation, patient safety and training opportunities. Methods: A retrospective cohort comparison of all free-flap breast reconstruction cases conducted at a single centre by five consultant plastic surgeons in the period May 2016–May 2020. Results: A total of 281 patient records were used for analysis; 146 cases were dual consultants compared with 135 single consultants, representing 186 and 158 free flaps, respectively. Patient demographics were near identical in terms of patient age, BMI and ASA grade. Operating times were significantly reduced for both unilateral (mean reduction 59.49 min) and bilateral cases (mean reduction 38.14 min) with the presence of dual consultants. The mean length of stay for dual-consultant cases was on average 0.35 days less than for single consultant cases ( p = 0.04). Dual-consultant case complications were less severe than those of single consultant cases (mean Clavien-Dindo severity 1.35 vs 0.96, p = 0.05). The rates of trainee one-to-one consultant training were increased in dual-consultant cases when preparing vessels (0.08 vs 0.35, p =<0.01) and performing anastomosis (0.63 vs 0.77, p = 0.03). Conclusions: DCO for complex breast reconstruction confers significant benefits to operating time, list utility and patient safety whilst protecting training opportunities for trainees. Plastic surgery departments looking to redesign services in the post-SARS-CoV-19 era should consider its adoption into their enhanced recovery protocols.